2021
DOI: 10.3389/fendo.2021.638615
|View full text |Cite
|
Sign up to set email alerts
|

The Repeatedly Elevated Fatty Liver Index Is Associated With Increased Mortality: A Population-Based Cohort Study

Abstract: AimsNon-alcoholic fatty liver disease (NAFLD) has a dynamic disease course, therefore repeated measurements of NAFLD status could have benefits rather than single one. The aim of this study was to investigate the effects of persistent NAFLD on the incidence of myocardial infarction (MI) and stroke and all-cause mortality by using repeated measurement of fatty liver index (FLI).MethodsAbout 3 million subjects who had undergone the health screening four times from 2009 until 2013 were included. NAFLD was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
(54 reference statements)
0
28
0
Order By: Relevance
“…Based on a median 29-year follow-up of a cohort of 1552 middle-aged men from the Kuopio Ischemic Disease Risk Factor Study, Setti et al [79] found that those men who had both renal hyperfiltration (RHF)which was associated with smoking -and fatty liver evaluated with FLI scores -which was associated with obesity -had the highest risk of mortality owing to all causes (HR = 1.96, 95%CI: 1.27-3.01). Conversely, having fatty liver associated with normal estimated glomerular filtration rate modestly increased the risk of all-cause mortality (HR = 1.35, 95%CI: 1.09-1.66).…”
Section: Does Fli Predict Mortality?mentioning
confidence: 99%
“…Based on a median 29-year follow-up of a cohort of 1552 middle-aged men from the Kuopio Ischemic Disease Risk Factor Study, Setti et al [79] found that those men who had both renal hyperfiltration (RHF)which was associated with smoking -and fatty liver evaluated with FLI scores -which was associated with obesity -had the highest risk of mortality owing to all causes (HR = 1.96, 95%CI: 1.27-3.01). Conversely, having fatty liver associated with normal estimated glomerular filtration rate modestly increased the risk of all-cause mortality (HR = 1.35, 95%CI: 1.09-1.66).…”
Section: Does Fli Predict Mortality?mentioning
confidence: 99%
“…Patients who either had incomplete or no data for the variables used in the analysis were excluded. Additionally, 809 patients who either conducted heavy alcohol consumption (alcohol drinking ≥ 2 days per week or alcohol intake of > 30 g/day), or had a previous history of liver cirrhosis (International Classification of Diseases 10th Revision (ICD)-10 codes: K70.2, K70.3, K70.4, and K74.6), alcoholic hepatitis (K70.1), chronic viral hepatitis B with delta-agent (B18.0), chronic viral hepatitis B without delta-agent (B18.1), and chronic viral hepatitis C (B18.2), liver and intrahepatic bile duct (C22) were excluded [ 22 , 23 ]. Finally, 3122 patients were included in this study (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These studies came from various countries across four continents. Seven studies (13,16,18,20,22,24,30) were conducted in North America (United States), seven (12,15,19,(27)(28)(29)31) in Asia (Japanese, Iran, Korea, China), five (17,21,23,25,26) in Europe (Italy, UK, Spain, Netherlands, Sweden, Germany), one (14) in Africa (Egypt). The sample size of included studies ranged widely, from 220 participants in an Iran case-control study to a study based on Korea nationwide health screening database of 95,84,399 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The mean age ranged between 48 and 67 years old, with years of follow up between 2.1 and 18.6 for cohort studies. With regard to the diagnosis of NAFLD, seven studies (12,14,15,17,19,25,31) used ultrasonography, four (18,(27)(28)(29) used fatty liver index, two studies (13, 23) used liver biopsy, two studies (16,20) used computed tomography, while remaining three studies (21,22,26) used international classification of diseases (ICD) code to detect NAFLD. Three studies (24,25,30) used NAFLD fibrosis score (NFS) and Fibrosis-4 score (FIB-4) to diagnose NAFLD-fibrosis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation